Galactosed and Reduction-Responsive Nanoparticles Assembled from Trimethylchitosan-Camptothecin Conjugates for Enhanced Hepatocellular Carcinoma Therapy - Chen Fu; Jingcan Qin; Xinlong Liu; Fei Kong (MDPI AG, 2022)
The targeted delivery of drugs to tumor cells and prevention of premature release before reaching the target is one of the key challenges to developing nanomedicines. In this paper, galactose decorated trimethyl chitosan (GT)-camptothecin (CPT) prodrug nanoparticles (GT-ss-CPT NPs) were prepared from GT-CPT conjugates linked by dithiodipropionic acid. The obtained GT-ss-CPT NPs were spherical with a particle size of 184.1 nm. GT-ss-CPT NPs displayed low drug release under physiological conditions, whereas efficient drug release was triggered by high GSH concentration. GT-ss-CPT NPs exhibited a higher antitumor effect both in vitro and in vivo than the free drug counterpart. More importantly, GT-ss-CPT NPs reduced the high systematic toxicity of CPT to tumor-bearing mice. In summary, GT-ss-CPT NPs can not only inhibit the premature release of CPT but also have a great potential for targeted hepatocellular carcinoma chemotherapy.